Thermodynamical Restrictions and Wave Propagation for a Class of Fractional Order Viscoelastic Rods - Teodor M. Atanacković; Sanja Konjik; Ljubica Oparnica; Dušan Zorica (Abstract and Applied Analysis)
We discuss thermodynamical restrictions for a linear constitutive equation containing fractional derivatives of stress and strain of different orders. Such an equation generalizes several known models. The restrictions on coefficients are derived by using entropy inequality for isothermal processes. In addition, we study waves in a rod of finite length modelled by a linear fractional constitutive equation. In particular, we examine stress relaxation and creep and compare results with the quasistatic analysis.